STRATEGIC ACCOUNTING Peran Strategis Akuntan Indonesia Dalam Penataan Ulang Sistem Keuangan Global - Jan Hoesada (Jurnal Akuntansi Bisnis, 2017)
Unification of the world's capital markets by IFRS convergence strategy was successful, because most of these countries to unite myself with global standards. IFRS GAAP 2009 is practically word for word translation and convergence will we do in the year 2012 to serve the public company which amounted to less than 1% of all business units in Indonesia. Almost 100% of business units in the country is marked private businesses UMKM, entrepreneurs are mostly Muslim, are now facilitated by ETAP Accounting Standards and Accounting Standards Sharia. Accounting is on economic development, not only the business of credit and debit financial statements, requires a new generation of counters with a way to think of State.Paper presented based on the idea of the various sources of literature references, the idea of recycling the original author and seminar papers as a member ekonotansi DSAK ideas and KSAP during the last 15 years, a variety of paper because the author is a lecturer and consultant management strategies in science. Key Word : Strategic Accounting, IFRS, Sistem Keuangan Global